Kami 8: SI+SA Exhibition: visualization of experience and comprehension in an artwork / Nur Adibah Nadiah Mohd Aripin, Sharifah Raudzah Syed Mahadi and Mohd Fawazie Arshad - Mohd Aripin, Nur Adibah Nadiah; Syed Mahadi, Sharifah Raudzah; Arshad, Mohd Fawazie (UiTM Perak Press, 2021)
SI+SA exhibition provided an opportunity and platform to the artists especially those who are also academicians to participate. It was an impactful exhibition both to the artists and the general public. Through visuals generated based on experience and comprehension, the artists were able to express themselves in their artwork which were closely related to two locations namely SI (Seri Iskandar), Perak + SA (Shah Alam), Selangor. The difference in locations was not a constraint for the artists to keep abreast of the current local art industry development. In fact, the distance provides an opportunity to stay ahead in the industry. Experience can be classified as a surge of idea for the artist to begin his step in producing artwork. Hence, experience does not only revolve around life events, but it also related to a social category as well as aesthetic element of art. It is the beginning of a complete production process according to the artists’ idea. From an observation on the SI+SA exhibition most artists produced artwork based on their experience, related to the main location selected. Analysis was made based on categories of visuals and artwork description that was inclusive of the artwork’s underlying meaning. Several artwork from SI+SA exhibition were made as references according to their categories. Visualising experience is not an easy task since the public’s understanding can be very subjective as it comes from different perspectives. Nevertheless, such understanding has a huge impact on an artwork’s appreciation.